2012
DOI: 10.3389/fpls.2012.00244
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Molecular Characterization, and Mapping of Four Rose MLO Orthologs

Abstract: Powdery mildew is a major disease of economic importance in cut and pot roses. As an alternative to conventional resistance breeding strategies utilizing single-dominant genes or QTLs, mildew resistance locus o (MLO)-based resistance might offer some advantages. In dicots such as Arabidopsis, pea, and tomato, loss-of-function mutations in MLO genes confer high levels of broad-spectrum resistance. Here, we report the isolation and characterization of four MLO homologs from a large rose EST collection isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…It is probable that the molecular mechanism is common in more dicotyledonous and monocotyledonous plants. In rose, MLO orthologs are found in an EST library (Kaufmann et al 2012). Recessive inherited mlo (loss-of-function) mediates broad-spectrum resistance in these species at the preinvasive stage and leads to early termination of pathogenesis (H€ uckelhoven and Pangstruga 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the molecular mechanism is common in more dicotyledonous and monocotyledonous plants. In rose, MLO orthologs are found in an EST library (Kaufmann et al 2012). Recessive inherited mlo (loss-of-function) mediates broad-spectrum resistance in these species at the preinvasive stage and leads to early termination of pathogenesis (H€ uckelhoven and Pangstruga 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequence (5#-3#) UNAFold (version 3.4; RNA Institute, Albany, NY) software (Bustin et al, 2009). Because each rose Mlo gene has more than one allele (Kaufmann et al, 2012), the primers for each Mlo gene were designed to match only one allele (their sequences are the same as GenBank no. JX847131-JX847134) using Beacon Designer (version 8.0; Premier Biosoft International, Palo Alto, CA) software with the following specifications: optimal annealing temperature at 58 ± 2°C, optimal primer length of 18-24 nucleotides, optimal amplicon length of 80-300 bp, content of guanine and cytosine between 45% and 55%.…”
Section: Genbank Accession Nomentioning
confidence: 99%
“…So far, four Mlo homologs RhMLO1-RhMLO4 were isolated from rose leaves (Kaufmann et al, 2012). Phylogenetic analysis showed that all Mlo genes from dicots for which a function in powdery mildew-host interaction has been experimentally demonstrated fall into one phylogenetic clade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An MLO gene was first identified in barley [3] and currently, a varying number of MLO genes have been identified in Arabidopsis, Medicago truncatula, chickpea, rice, maize, wheat, soybean, cucumber, tomato, rose, grapevine, peach, apple, sweet orange, cultivated Solanaceae, Brachypodium, and Cucurbitaceae species respectively [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Although the biological functions of MLO genes are not yet completely known, they act as suppressors of defense responses.…”
Section: Introductionmentioning
confidence: 99%